2015
DOI: 10.3126/jonmc.v4i1.12811
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-Epidemiological Profile and Outcome of Poisonous Snake Bites in Children using the WHO Treatment Protocol in Western Nepal

Abstract: Background: Snake bite among children is an important public health problem in many tropical and subtropical countries. Limited studies are found on snake-bite in Nepal using the WHO snake-bite management guidelines. This study assessed the clinico-epidemiological profile and their outcome in snake-bite among children using the WHO Guidelines for treatment of snake bite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…In this study, 115 (57.5%) of cases were bitten on the lower limb, 85(42.5%) on upper limb. Similar observations are reported in India and world literature but unusual sites like head, trunk was not observed in present study [20]. In rural India, due to mentality of the people to seek treatment from quacks they present to the hospital late after the bite and because of lack of transport facility during night hours the primary center is not approachable.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, 115 (57.5%) of cases were bitten on the lower limb, 85(42.5%) on upper limb. Similar observations are reported in India and world literature but unusual sites like head, trunk was not observed in present study [20]. In rural India, due to mentality of the people to seek treatment from quacks they present to the hospital late after the bite and because of lack of transport facility during night hours the primary center is not approachable.…”
Section: Discussionsupporting
confidence: 89%
“…11,12 However this finding was opposite to many other studies. 3,5,13 In this study, incidence of snake bite was found more in rural area (91%) and least from urban area (9%). This finding was similar to other study.…”
Section: Discussionmentioning
confidence: 49%
“…This finding was similar to other study. 3,7,9,14 Dwelling conditions in rural areas of Nepal is more favorable for habitation of snakes and most people are engaged in agriculture work, which leads to more snake bites. Most patients visited are from Terai regions (84%) compared to hilly regions (16%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations